Membaca Ulang Studi Hadis Di Barat: Analisis Shifting Paradigm Terhadap Evolusi Kritik Orientalis - Arif Budiman (Al-Mu'tabar, 2025)
This article aims to analyze the paradigm shift in Western hadith studies using Thomas Kuhn’s theoretical framework of shifting paradigm. The study focuses on tracing the epistemological evolution from the paradigm of orientalist skepticism toward a more critical-constructive approach that demonstrates openness to the authenticity of hadith. This research adopts a qualitative method through a library-based study. Data were collected from primary sources, including the works of Ignaz Goldziher, Joseph Schacht, G.H.A. Juynboll, and Harald Motzki. A historical-comparative analysis was employed to examine the methodological transitions across different periods. The findings reveal a significant shift in how Western scholars conceptualize hadith authenticity—from an a priori rejection to a more contextual and multidisciplinary academic engagement. Furthermore, within Western scholarship, hadith studies have expanded into a broader epistemological discourse. In this regard, hadith is no longer viewed solely as a site of methodological contention but also as a dialogical space between Western critical inquiry and the Islamic intellectual tradition, contributing to the development of a more inclusive and dynamic contemporary hadith scholarship.